Innovations on scientific support of grain crop breeding for resistance to diseases and pests - Krut , M. (Interdepartmental Thematic Scientific Collection of Phytosanitary safety, 2020)
Goal. Database formation of innovations in the scientific provision of breeding crops for resistance to pathogens and pests — grounds for creating sustainable varieties. Methods. Analysis of innovative development of the Institute of Plant Protection of the National Academy of Agrarian Sciences of Ukraine and other institutions of the Scientific and Methodological Center «Protection of Plants» for 2001—2020. Isolation of those relating to the problem of grain crops’ resistance to pests and pathogens. Results. Methods of selection of wheat and barley for resistance to basic pathogens of diseases and methodology for assessing the stability of winter wheat stability to pests to create complex resistant varieties are developed. A database for the resistance of corn hybrids against main pests was created. Methods of determining the stability of grain crops to high and low temperatures are developed. A collection of samples of wild relative of wheat Aegilops biuncialis L. that are sources of new genes for plant resistance to diseases and pests was created. Genes of resistance of soft winter wheat to diseases by DNA markers have been identified. A set of varieties of winter wheat with group and complex resistance to diseases and pests has been formed. Physiological and biochemical mechanisms of soybean resistance to pathogens of diseases are established. Collection of soybean lines is created on the basis of complex resistance to white rot and anthracnosis. The varieties and selection numbers of spring barley, oats, resistant to basic diseases, as well as rice varieties that are resistant to pathogens of diseases and pests were identified. Resistance to viral diseases has been found in barley plants. Conclusions. The established innovations can be widely used by breeding centers and other scientific institutions of the agrarian profile when of output sustainable grain and leguminous grain crops. In this case, the timing of the selection process can be accelerated by 40—60%.